CURRENT STATUS ON CACAO DISEASE INCIDENCE IN CENTRAL SULAWESI - Nur Edy; Margaret Angelia; Irwan Lakani; Johanis Panggeso (Tadulako University, 2019)
Central Sulawesi is largest of cocoa bean producer in Indonesia. However, cacao production constrained by important diseases. Currently, data about cacao been damage due to pathogen infection have not been updated. This study observed the incidence of major diseases in cacao plantations, included pod rot, canker, and vascular-streak dieback (VSD). The study was situated at the largest cacao plantation in Central Sulawesi, in Ampera, Berdikari, Bahagia, Ue Rani, and Sejahtera villages in Palolo District, Sigi Regency. The observation pronounced that the cacao trees in the study sites were infected by the pathogens of pod rot, canker, and VSD with different incidence levels. VSD was a disease with the highest incidence and distribution in the cacao plantations. Besides, this study also described the symptom of the disease.